Effects of Inter-Basin Water Transfer Project Operation for Emergency Water Supply - Choi, Youngje; Ahn, Jaehwang; Ji, Jungwon; Lee, Eunkyung; Yi, Jaeeung (Water Resources Management, 2020)
In South Korea, rainfall deficits lasting for three years (2014–2017), have decreased the reservoir storage level. The Boryeong reservoir, located in the Geum River western sea basin, recorded the lowest reservoir storage. The Boryeong water transfer project has supplied water resources to the east side of the basin. This is an emergency water supply project operated when there is a water supply shortage in the reservoir. It is essential to use appropriate settings for the operation scheme. In this study, a reservoir simulation model was built by applying a water supply adjustment standard, which reduces the water supply when reservoir storage is decreased to a specific level. Four operation cases (no operation, continuous operation, and two temporary operations) were used to analyze the effects of the project. The temporary operations activate when the reservoir storage decreases. The volumetric reliability of the water supply is enhanced by 1.8–2.2% in the temporary operation cases. This study used cost-benefit analysis to analyze the two temporary operation cases. Operating the transfer project when reservoir storage goes below a certain level is more efficient than other cases.
Keywords: Continuous operation; Inter-basin water transfer; Operation schemes; Reservoir simulation model; Volumetric reliability; Water supply projects; Water supply shortages; Water transfer projects; Emergency water supply; Inter-basin transfer; Reservoir operation; Water shortage